Rearranged Endogenized Plant Pararetroviruses as Evidence of Heritable RNA-based Immunity - Valli, Adrian Alejandro (2023)
Eukaryotic genomics frequently revealed historical spontaneous endogenization events of external invading nucleic acids, such as viral elements. In plants, an extensive occurrence of endogenous plant pararetroviruses (EPRVs) is usually believed to endow hosts with an additional layer of internal suppressive weaponry. However, an actual demonstration of this activity remains speculative. We analyzed the EPRV component and accompanying silencing effectors of Solanum lycopersicum, documenting that intronic/intergenic pararetroviral integrations bearing inverted-repeats fuel the plant’s RNA-based immune system with suitable transcripts capable of evoking a silencing response. A surprisingly small set of rearrangements explained a substantial fraction of pararetroviral-derived endogenous smallinterfering (si)RNAs, enriched in 22-nt forms typically associated with anti-viral post-transcriptional gene silencing. We provide preliminary evidence that such genetic and immunological signals may be found in other species outside the genus Solanum. Based on molecular dating, bioinformatics, and empirical explorations, we propose that homology-dependent silencing emerging from particular immuno-competent rearranged chromosomal areas that constitute an adaptive heritable trans-acting record of past infections, with potential impact against the unlocking of plant latent EPRVs and cognate-free pararetroviruses.